Proposal of a method to evaluate the in-situ oxidation of polyphenolic during the cocoa drying. Issue 3 (1st February 2022) - Alean, Jader; Chejne, Farid; Ramírez, Say; Rincón, Edgar; Alzate-Arbelaez, Andrés F.; Rojano, Benjamin
Abstract: In this work, the oxidation of polyphenols during drying of cocoa beans by using microwaves (MWs), applied in an ON-OFF mode, was studied. Phenolic compounds were quantified in cocoa beans before and after drying. Total phenolics content was analyzed by using some analytical techniques such as Fourier transform infrared (FTIR) spectroscopy, and high-performance liquid chromatography (HPLC). To study the oxidation process in-situ, an innovative methodology was proposed based on the counting of the coloring of the polyphenols contained in the parenchyma cells of the cocoa beans (cotyledon). The level of coloration in the inner zone and the surface of the dried cocoa beans showed that degradation of polyphenol compounds during the drying does not obey to a transport mechanism (diffusion), but in-situ oxidative processes.